EFEKTIVITAS PEMBIAYAAN KUR SYARIAH TERHADAP PERKEMBANGAN INDUSTRI KREATIF DI KOTA MAKASSAR (Studi Kasus di PT Pegadaian Cabang Bontoala Kota Makassar) - Marni Mansur; Hasnidar Hasnidar; Adi Adi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2025)
The aim of the research is to find out and analyze 1) KUR Syari'ah financing procedures at PT. Pawnshop Bontoala Makassar Branch. 2) Effectiveness of KUR Syari'ah Financing at PT. Pegadaian Bontoal Branch in improving the Creative Industry in Makassar City. The research is qualitative research with a case study approach. The population of this research is all Pegadaian customers who receive KUR Syariah funding assistance. The sampling technique in this research is to use the Snowball sampling method or chain-referral sampling method. Data analysis techniques are deductive and inductive analysis. The research results are; 1). Syari'ah KUR Financing Procedure at PT. Pawnshop Bontoala Makassar Branch is very simple starting from; a) customer fills in the application form, a) submits required documents, c) survey, d) signs the contract, e) Rahin (Customer) receives sharia KUR disbursement within 3 working days if all requirements are met. 2) KUR Syariah pawnshop financing is effective in increasing the Creative Industry in Makassar City. This can be proven through 4 elements of researcher observation, namely; Business capital, sales turnover, profits and working hours have all increased significantly.